Inelastic cyclic response of RBS connections with jumbo sections - Bompa, D.V.; Elghazouli, A.Y.; Bogdan, T.; Eatherthon, M.R.; Leon, R.T. (Engineering structures, 2023)
•RBS connections with large sections under cyclic loading.•Validation of numerical procedures against full-scale RBS connections tests.•Detailed nonlinear parametric investigations on RBS connections.•Influence of the RBS-to-column capacity ratio and RBS detailing on the response.•Design expressions and recommendations for connections with large sections. This paper examines the cyclic performance of reduced beam section (RBS) moment connections incorporating larger member sizes than those allowed in the current seismic provisions for prequalified steel connections, through experimentally validated three-dimensional nonlinear numerical assessments. Validations of the adopted nonlinear finite element procedures are carried out against experimental results from two test series, including four full-scale RBS connections comprising large structural members, outside the prequalification limits. After gaining confidence in the ability of the numerical models to predict closely the full inelastic response and failure modes, parametric investigations are undertaken. Particular attention is given to assessing the influence of the RBS-to-column capacity ratio as well as the RBS geometry and location on the overall response. The numerical results and test observations provide a detailed insight into the structural behavior, including strength, ductility, and failure modes of large RBS connections. It is shown that connections which consider sections beyond the code limits, by up to two times the weight or beam depth limits, developed a stable inelastic response characterized by beam flexural yielding and inelastic local buckling. However, connections with very large beam sections, up to three-times the typically prescribed limits, exhibited significant hardening resulting in severe demands at the welds, hence increasing susceptibility to weld fracture and propagation through the column. The findings from this study point to the need, in jumbo sections with thick flanges, for a deeper RBS cut than currently specified in design, to about 66% of the total beam width. This modification would be required to promote a response governed by extensive yielding at the RBS while reducing the excessive strain demands at the beam-to-column welds. Moreover, for connections incorporating relatively deep columns, it is shown that more stringent design requirements need to be followed, combined with appropriate bracing outside the RBS, to avoid out-of-plane rotation.